Effect of different analyte diffusion/adsorption protocols on SERS signals. (18th July 2018) - Li, Ruoping; Petschek, Rolfe G.; Han, Junhe; Huang, Mingju
ABSTRACT: The effect of different analyte diffusion/adsorption protocols was studied which is often overlooked in surface-enhanced Raman scattering (SERS) technique. Three protocols: highly concentrated dilution (HCD) protocol, half–half dilution (HHD) protocol and layered adsorption (LA) protocol were studied and the SERS substrates were monolayer films of 80 nm Ag nanoparticles (NPs) which were modified by polyvinylpyrrolidone. The diffusion/adsorption mechanisms were modelled using the diffusion equation and the electromagnetic field distribution of two adjacent Ag NPs was simulated by the finite-different time-domain method. All experimental data and theoretical analysis suggest that different diffusion/adsorption behaviour of analytes will cause different SERS signal enhancements. HHD protocol could produce the most uniform and reproducible samples, and the corresponding signal intensity of the analyte is the strongest. This study will help to understand and promote the use of SERS technique in quantitative analysis. Abstract :